Pengaruh Kinerja Laporan Keuangan Bank Pengkreditan Rakyat Syariah Dan Konvesional Terhadap Pertumbuhan Ekonomi Indonesia - Usep Achmad Bahauddin; Budi Andru (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
The development of the financial sector can affect the country's economic growth. Reflecting on this discussion in the era of the covid-19 pandemic - the new normal era 2019-2021 Indonesia seems important for academics. This study aims to determine the effect of Islamic rural banks (BPRS) and conventional (BPRK) on Indonesia's economic growth. Multiple Linear Regression Analysis was used as a research method with the classical assumption test stages and multiple linear regression tests. The aids in data management use the JASP (Jeffreys' Amazing Statistics Program) application. Secondary data is collected from published sources of bank financial performance reports on the OJK website and the value of economic growth through BPS Indonesia for the year 2019-2021. Secondary sampling with 30 data observations came from BPRS and BPRK provinces in Indonesia that attached the 2019-2021 routine financial reports. Financial performance parameters with Return On Assets (ROA) are used as independent research variables, namely X1 (ROAS) and X2 (ROAK), as well as the dependent variable Y (PEI) with the results H1 is accepted (X1 is significant to Y), H2 is rejected (X2 is not significant to Y). Y), H3 is accepted (X1 and X2 are simultaneously significant to Y), and R2 (Coefficient of Determination) is 23.3%. The contribution in this study is to determine the effect of the performance of the financial statements of Islamic rural credit banks (BPRS) and conventional (BPRK) on Indonesia's economic growth and provide suggestions for future research.